Prácticas de alimentación complementaria en niños dentro del primer año de vida - Parada, Cristina Maria Garcia de Lima [UNESP]; Carvalhaes, Maria Antonieta de Barros Leite [UNESP]; Jamas, Milena Temer [UNESP] (My University, 2007)
This study aimed to investigate complementary feeding practices during children's first year of life in Botucatu, SP, Brazil. Practices were described according to the age range and the breastfeeding (BF) practice. Data were collected during a multi-vaccination campaign through the interview of 1,238 individuals who accompanied children younger than one year old being vaccinated. Differences associated with the BF situation were identified by the chi-square test and Fisher's exact test. The early introduction of complementary food was observed, which led to the low frequency of exclusive breastfeeding (36.9% <4 months). Children younger than 4 months old consumed tea (30.7%); children between 4 and 6 months old consumed fruits (54.1%), soups (39.9%) and home-made food (19.2%). Juice was offered only to 15.2% of children younger than 4 months old who were completed weaned, 60% of the children was offered water. Data show that the consistence of the food consumed was inappropriate: children between 6 and 8 months old were offered the family's regular food (48.8%) and children older than 8 months (71.6%) were offered soup. Therefore, interventions focused on complementary feeding are justified on the city.
Complementary feeding practices to children during their first year of life
Keywords: Breast feeding; Milk, human; Supplementary feeding; Brazil; breast feeding; cross-sectional study; feeding behavior; human; infant; infant nutrition; newborn; questionnaire; statistics; Breast Feeding; Cross-Sectional Studies; Feeding Behavior; Humans; Infant; Infant Nutrition Physiology; Infant, Newborn; Questionnaires